Brain Plasticity Effects of Neuromodulation Against Multiple Sclerosis Fatigue - Tecchio, Franca; Cancelli, Andrea; Cottone, Carlo; Ferrucci, Roberta; Vergari, Maurizio; Zito, Giancarlo; Pasqualetti, Patrizio; Filippi, Maria Maddalena; Ghazaryan, Anna; Lupoi, Domenico; Smits, Fenne M.; Giordani, Alessandro; et al. (Frontiers in Neurology, 2015)
Rationale We recently reported on the efficacy of a personalized transcranial direct current stimulation (tDCS) treatment in reducing MS fatigue. That result supports the notion that interventions targeted at modifying unbalanced interactions within the sensorimotor network could represent valid non-pharmacological treatments. Objective The present work aimed at assessing whether the mentioned intervention also induces changes in the excitability of cortical areas. Method Two separate groups of fatigued MS patients were given a 5-day tDCS treatments targeting respectively the whole body somatosensory areas (S1wb) and the hand sensorimotor areas (SM1hand). The study had a double blind, sham-controlled, randomized, cross-over (Real vs. Sham) design. Before and after each treatment, we measured fatigue levels (by the modified Fatigue Impact Scale, mFIS), motor evoked potentials (MEPs) in response to transcranial magnetic stimulation (TMS) and somatosensory evoked potentials (SEP) in response to median nerve stimulation. We took MEPs and SEPs as measures of the excitability of the primary motor area (M1) and the primary somatosensory area (S1) respectively. Results The Real S1wb treatment produced a 27% reduction of the mFIS baseline level, while the SM1hand treatment showed no difference between Real and Sham stimulations. M1 excitability increased on average 6 % of the baseline in the S1wb group and 40% in the SM1hand group. Observed SEP changes were not significant and we found no association between M1 excitability changes and mFIS decrease. Conclusions The tDCS treatment was more effective against MS fatigue when the electrode was focused on the bilateral whole body somatosensory area. Changes in S1 and M1 excitability did not correlate with symptoms amelioration. Significance The neuromodulation treatment that proved effective against MS fatigue induced only minor variations of the motor cortex excitability, not enough to explain the beneficial effects of